Electronic Mail Defining a Role for the U.S. Postal Service - McLaughlin, John F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Threatened by competitive diversification and by increasing costs, the United States Postal Service has investigated two potential cost reducing systems: (1) a microsystem which would provide electronic facsimile transmission between major markets and (2) a macrosystem which could take digital input such as utility bills and deliver a hardcopy to receivers anywhere in the country. The first system would be most appropriate for business-to-business deliveries, but the most lucrative portion of this market will probably be captured by independent competitors. The second system requires a massive capital investment, and it would probably still require hand-carried deliveries, the most expensive component of mail handling. If customers are willing to accept electronic output, impressive economies of scale can be obtained through the use of electronic systems. (EMH)
ERIC Note: Paper presented at the Telecommunications Policy Research Conference (Airlie, Virginia, April 21-24, 1976).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Costs; Delivery Systems; Facsimile Transmission; Information Dissemination; Online Systems; Speeches; Telecommunications; Postal Service; Mail Delivery; Speeches/Meeting Papers